EARLY EDUCATION CAN HELP PREVENT AND MANAGE POISONING CASES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, March 2015 Poisoning incidents can be prevented or reduced if members of the public are better informed of its hazards and consequences.